Decisão do Superior Tribunal de Justiça altera o entendimento do Tribunal de Justiça de São Paulo a respeito da regulação de seguros e planos de saúde = A decision by the Brazilian Superior Court changes the understanding of the Court of Justice of São Paulo regarding the regulation of private health insurance and plans - Robba, Rafael (2022)
DOI: https://doi.org/10.11606/issn.2316-9044.rdisan.2022.174896